2014
DOI: 10.1155/2014/904046
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Neurocysticercosis: Usefulness of Antibody Response in Cysticidal Treatment Follow-Up

Abstract: Serum and urine samples were collected from 33 NCC patients before the albendazole treatment, 3–6 and 12 months PT. At 3 months PT, 24 (72.7%) patients had no detectable CT/MRI lesions and 9 (27.2%) patients had persistent lesions. Antibody response to crude soluble extract (CSE), excretory secretory (ES), and lower molecular mass (LMM) (10–30 KDa) antigenic fraction of T. solium cysticerci was detected in serum and urine samples by ELISA. Before the treatment, out of 33 NCC children, 14 (42.4%), 22 (66.6%), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…The LLGP‐EITB, however, is technically complicated, requires sophisticated laboratory capacity and is not widely available. Despite previously published data pointing to inferior diagnostic performance , many investigators still use antibody detection by ELISA for diagnostic purposes . Commercial ELISA assays are offered by most diagnostic laboratories in the United States and Europe, and globally ELISA for antibody is the most commonly performed serologic assay for cysticercosis.…”
Section: Introductionmentioning
confidence: 99%
“…The LLGP‐EITB, however, is technically complicated, requires sophisticated laboratory capacity and is not widely available. Despite previously published data pointing to inferior diagnostic performance , many investigators still use antibody detection by ELISA for diagnostic purposes . Commercial ELISA assays are offered by most diagnostic laboratories in the United States and Europe, and globally ELISA for antibody is the most commonly performed serologic assay for cysticercosis.…”
Section: Introductionmentioning
confidence: 99%
“…In the present investigation, samples revealing anti-cysticercus antibodies against ESA (30.76 %) were on the lower side compared to Sahu et al (2015) , who observed 45 % seropositivity among ocular CC cases. Antibody response to ESA in confirmed NCC patients has been observed to the tune of 88.2 % and 66.6 % among 34 and 36 cases from Pondicherry ( Sahu et al , 2009 ) and Chandigarh ( Atluri et al , 2014 ) of India, respectively. Molinari et al (2002) observed an anti-cysticercus antibody against ESA in the cerebrospinal fluid (CSF) of 24 (17 %) of patients out of 91 with a neurological disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Una localización que puede ser diagnosticada durante la exploración física es la ocular, ya que, al observar el fondo de ojo, se puede ver el parásito en el espacio subretiniano o en el humor vítreo. Esta presentación puede poner en riesgo la visión, por la inflamación y degeneración de los quistes o el desprendimiento de la retina (14,16).…”
Section: Discussionunclassified